Implementation of the sepsis-3 definition in German university intensive care units: A survey - Keppler, Ulrich; Schmoch, Thomas; Siegler, Benedikt Hermann; Weigand, Markus A.; Uhle, Florian (Der Anaesthesist, 2018)
BackgroundThe old definition of sepsis was replaced by Sepsis-3 in February 2016. The new screening diagnostic tools sequential organ failure assessment (SOFA) score and quick SOFA (qSOFA) score were incorporated into the definition. The resulting scientific controversy led to several retrospective and prospective evaluations. In contrast no evaluation of the state of play of national implementation of Sepsis-3 has been conducted so far.ObjectiveThe aim of this study was to capture the current situation in German academic intensive care units 1 year after the implementation of Sepsis-3.MethodsAn internet-based questionnaire consisting of 22 items was developed. The identification of eligible departments was performed by an online search of the homepages of all university hospitals located in Germany. Departments regardless of the discipline with an explicit indication of involvement in intensive care were extracted. The link to the internet-based questionnaire was sent to all identified departments on 22 February 2017 and was accessible for 19 days.ResultsOut of 259 departments 76 answered the online survey. The response rate was 29.3% from 13 specializations. Anesthesiology, internal medicine and general surgery were the three main participants in this study. The majority of intensive care units (54.75%) treated more than 100 patients with sepsis or septic shock annually and more than 30% treated more than 250 patients. While 76.7% of respondents had a standard operating procedure, 55% of those were based on the Sepsis-3 definition. When asked to rate the usefulness of the Sepsis-3 definition, answers were heterogeneous with a slight tendency towards a higher usefulness and the majority (72.9%) were in favor of Sepsis-3 being included in the national S2K guidelines.ConclusionThe results demonstrate the heterogeneity of Sepsis-3 implementation in German intensive care units. Sepsis-3 is finding its way but there is a need for standardized implementation.
Gesehen am 24.10.2019